2017
DOI: 10.4081/audiores.2017.176
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Otological and Peripheral Nerve Involvement in Fabry Disease

Abstract: Fabry disease (FD) is an X-linked lysosomal storage disease, with multisystemic glycosphingolipids deposits. Neuro-otological involvement leading to hearing loss and vestibular dysfunctions has been described, but there is limited information about the frequency, site of lesion, or the relationship with peripheral neuropathy. The aim was to evaluate the presence of auditory and vestibular symptoms, and assess neurophysiological involvement of the VIII cranial nerve, correlating these findings with clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…An extension of latency as sign of a neurogenic or central pathology was found 12 times in cVEMPs and 13 times in oVEMPs. These results are comparable to a recently published study with a mixed-gender group of 36 Fabry patients [ 37 ]. For the first time, it was reported on pathological cVEMPs in 45% of the patients, also occurring in nonsymptomatic patients.…”
Section: Discussionsupporting
confidence: 90%
“…An extension of latency as sign of a neurogenic or central pathology was found 12 times in cVEMPs and 13 times in oVEMPs. These results are comparable to a recently published study with a mixed-gender group of 36 Fabry patients [ 37 ]. For the first time, it was reported on pathological cVEMPs in 45% of the patients, also occurring in nonsymptomatic patients.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, vibration sense and position sense are mostly normal but there may be abnormalities in pain and temperature sensation. Despite this lack of large fiber involvement, Carmona et al [24] found evidence of objective vestibular dysfunction in approximately half of their patient cohort, and similarly approximately 60% had evidence of hearing loss on pure tone audiogram. In the aggregate, 70% of subjects had combined cochlear and vestibular dysfunction.…”
Section: What Do I Do If My Patient Has a Somatosensory Deficit With ...mentioning
confidence: 92%
“…Hearing loss, tinnitus, and vertigo are more prevalent in patients with FD than in the age-matched general population,1,2,95 but the underlying etiology remains unclear in many patients 96. The age onset of FD-related neuro-otologic symptoms is earlier, and their clinical severity is higher in hemizygous males than in heterozygous females.…”
Section: Other Common Later-onset Nondiagnostic Manifestations Of Fdmentioning
confidence: 99%